A novel high‐frequency floating resonant gate driver with reduced gate driving loss. Issue 14 (3rd July 2022) - Gu, Cheng; Qian, Qinsong; Wang, Yanting; Ding, Song; Zhou, Ziyan; Dong, Tianhao; Sun, Weifeng
Abstract: Conventional resistive gate driving circuits suffer from significant recovery gate driving losses, especially at MHz ranges. The increasing gate driving losses brought by high switching frequency place a limitation to the high power density converter design. This paper proposes a novel floating resonant gate driver which maintains high efficiency at several megahertz operating frequency. The gate loss reduction is achieved by adopting a resonant process with driving power recycling. Part of the gate driving power can be recycled to a gate driving capacitor in the gate driving loop during charging and discharging. The proposed gate driver merges the merits of fast switching speed and low gate driving losses. A prototype of LLC power converter with the proposed floating resonant gate driver operating at 3.5 MHz is implemented. According to the experimental verification, the proposed gate driver realized a driving loss reduction by 70% and theoretical analysis is in good agreement with experimental results.